COMPARISON OF SUBCUTANEOUS EXTRALESIONAL AND INTRALESIONAL TRIAMCINOLONE INJECTION FOR THE TREATMENT OF CHALAZION: Triamcinolone Injection for Treatment of Chalazion - Parveen, Shagufta; Babar, Zaheerud Din; Ishaq, Mazhar; Islam, Qamar ul (Pakistan Armed Forces Medical Journal, 2015)
Objective: To compare the efficacy of injection of extralesional subcutaneous triamcinolone and intralesional triamcinolone in the treatment of primary chalazion. Study Design: Randomized controlled trial. Place and Duration of Study: Armed Forces Institute of Ophthalmology (AFIO) Rawalpindi, from 1st September 2011 to 31st March 2012. Patients and Methods: Ninety two patients fulfilling the selection criteria were randomly divided into two groups of 46 patients each group A intralesional triamcinolone (IT) patients received a single extralesional subcutaneous triamcinolone injection while group B extralesional triamcinolone (ET) patients received intralesional triamcinolone injection. Main outcome measure was reduction in chalazion size to 2mm or smaller after steroid injection at 4 weeks follow up visit. The size of chalazion was measured at baseline and then at 2 weeks and 4 weeks post steroid injections. Data analysis was done by “statistical package for social sciences (SPSS) version 13.0 for windows. Results: Both the groups were age matched with mean age of 30.46 ± 10.09 years in group A and 29.13 ± 6.04 yrs in group B. Among the subjects, there were 64 male and 28 female patients. Out of 92 patients, resolution was seen in 84.8% (39 out of 46 cases) in ET group and 82.6% (38 out of 46 cases) in IT group at 4 weeks follow up that was not statistically significant (p = 0.45). Conclusion: Injection of extralesional subcutaneous triamcinolone is as effective as intralesional triamcinolone in treatment of chalazion.